FACTORS INFLUENCING THE PHOTOCATALYTIC DECOLORIZATION OF METHYLENE BLUE IN THE PRESENCE OF NATURAL IRON OXIDE AND OXALIC ACID UNDER UV IRRADIATION. (Sciences & Technology. A, exactes sciences, 2014)
In this work, the methylene blue (MB) heterogeneous photodegradation was investigated in the natural iron oxide (NIO) and oxalic acid process under UV irradiation. The adsorption of MB onto the surface of NIO was found favorable by the Langmuir approach. Under the operating conditions of this study, the photo-Fenton reaction was set up in co-presence of NIO and Oxalic Acid (OA). Where, the total degradation of MB was achieved in 90 min. The mechanism of MB photodegradation was discussed and the use of 2.0 % of tertiobutanol as a scavenger of •OH confirmed their intervention in the reaction. The effect of oxygen and hydrogen peroxide were investigated, the results demonstrated that the oxygen was necessary in the MB photodegradation and that the optimum concentration of hydrogen peroxide was found to be 5x10-4 M. measuring the chemical oxygen demand (COD) demonstrates the effectiveness of our natural iron oxide in the degradation of organic pollutants.